2014
DOI: 10.1016/j.apenergy.2014.05.062
|View full text |Cite
|
Sign up to set email alerts
|

Using regression analysis to predict the future energy consumption of a supermarket in the UK

Abstract: h i g h l i g h t sEnergy consumption of supermarket depends more on temperature than humidity. Multiple regression analysis is a flexible tool to consider for energy use prediction. Results show dramatic reduction in gas use and modest increase in electricity use. a b s t r a c tThe change in climate has led to an interest in how this will affect the energy consumption in buildings. Most of the work in the literature relates to offices and homes. However, this paper investigates a supermarket in northern Engl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
93
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 220 publications
(104 citation statements)
references
References 15 publications
1
93
1
1
Order By: Relevance
“…Many bottom-up regression models for energy demand modeling rely on the Princeton Scorekeeping Method [25], which describes the fundamental correlation between outdoor temperature and heating energy consumption. Recent studies using regression for modeling and predicting energy consumption often analyze hourly or sub-hourly energy meter data [26][27][28][29][30][31][32][33].…”
Section: Methods For Modeling Aggregate Hourly Energy Consumptionmentioning
confidence: 99%
“…Many bottom-up regression models for energy demand modeling rely on the Princeton Scorekeeping Method [25], which describes the fundamental correlation between outdoor temperature and heating energy consumption. Recent studies using regression for modeling and predicting energy consumption often analyze hourly or sub-hourly energy meter data [26][27][28][29][30][31][32][33].…”
Section: Methods For Modeling Aggregate Hourly Energy Consumptionmentioning
confidence: 99%
“…Sustainability 2017, 9, 0127 10.3390/su10010127 7 of 22 accepted minimum R 2 value of 0.7 specified in modelling work [38], it can be suggested that the kinetic relationship represented by the linear plot is sufficient to predict the yield of FAs generated during subcritical hydrolysis and can be employed to achieve the aims of this paper. This implies therefore that the kinetic parameters (Ahy and Ehy), can be easily estimated by plotting Ln khy, which is obtained from the graph slopes in Figure 4 against 1/T such that the slope and the intercept will give the Ehy/R and the Ahy respectively.…”
Section: Kinetic Modelling Of Subcritical Lipid Hydrolysis and Supercmentioning
confidence: 99%
“…Different types of mathematical models have been used in the past to estimate the space heating/cooling energy use of buildings. Statistical approaches such as regression [13][14][15], Artificial Neural Networks [16], and Support Vector Machines [17] are found in the literature for energy predictions. A combined physical and statistical approach has been used in [18].…”
Section: The Test Buildingmentioning
confidence: 99%